Copper‐Catalyzed Aerobic Oxidative Inert CC and CN Bond Cleavage: A New Strategy for the Synthesis of Tertiary Amides. Issue 38 (5th August 2014) - Chen, Xiuling; Chen, Tieqiao; Li, Qiang; Zhou, Yongbo; Han, Li‐Biao; Yin, Shuang‐Feng
Abstract A copper‐catalyzed aerobic oxidative amidation reaction of inert CC bonds with tertiary amines has been developed for the synthesis of tertiary amides, which are significant units in many natural products, pharmaceuticals, and fine chemicals. This method combines CC bond activation, CN bond cleavage, and CH bond oxygenation in a one‐pot protocol, using molecular oxygen as the sole oxidant without any additional ligands.